USADA BHUDA KACAPI: BALINESE TRADITIONAL THERAPY (USADA) LITERARY TEXT - Jirnaya, I Ketut; Suastika, I Made; Cika, I Wayan; Weda Kusuma, I Nyoman (e-Journal of Linguistics; Vol. 5. Juli 2011 No. 2)
Usada Budha Kacapi (abbreviated to UBK) text, which contains the basic Balinese traditional therapy, is a text which is in the form of narration. The Balinese traditional therapy ( usada ) texts generally contain collections of names of diseases, medicinal substances, and how to cure such diseases; however, the UBK is in the form of narration, containing characters, setting, themes, and literary language. The UBK text, after being edited, is recorded in a number of palm-leaf manuscripts. The title is the same but the content varies. Budha Kecapi is the main character, which has inspired many other writers; therefore, the works produced still use the same language units as used by Budha Kacapi. Such works are Budha Kacapi Cemeng, Budha Kacapi Putih , and Budha Kacapi Sastrasanga . It is this which has inspired the researcher to explore the UBK in order to know who and what Budha Kacapi is. In order to be able to identify the message transmitted to the reader or the community, and its totality, it is necessary to know, understand, and analyze the signs it contains. Therefore, two theories are used in this study; they are the theory of intertextuality and the theory of semiotics. The results of analysis show that the writers wish to teach and guide those who desire to be professional indigenous medical practitioners ‘dukun’, namely, the ones who are highly knowledgeable of traditional therapy, ethical and not easily defeated by diseases. That, according to Budha Kacapi, can be achieved through ‘ yogasastra ’. The indigenous medical practitioners should improve their quality through yoga (meditation) and aksara suci (holy scripts) as the means. A set of learning materials related to the basic knowledge needed by the indigenous medical practitioners are systematically organized, starting from how to recruit the prospective learners, the learning method, how to diagnose ( nenger ), the philosophy of life and death, the philosophy of diseases, the concept of being healthy and sick, the compensation, types of diseases, and how to cure diseases. As a whole, the UBK text contains the basic and advanced levels of learning materials for indigenous medical practitioners. The advanced level means that if they study the UBK text and are able to apply it properly, they will not by all means be defeated by diseases.
Keywords: diagnosis (nenger), philosophy of diseases, yogasastra, and professional indigenous medical practitioner.